Improvement in the Surveillance System for Livestock Diseases and Antimicrobial Use Following Operational Research Studies in Sierra Leone January–March 2023 - Samuel Alie Konteh; Fatmata Isatu Bangura (Turay); Amara Leno; Srinath Satyanarayana; Divya Nair; Mohamed Alpha Bah; Salam Saidu; David Sellu-Sallu; Sahr Raymond Gborie; Sorie Mohamed Kamara; Amadu Tejan Jalloh; Joseph Sam Kanu; et al. (Tropical Medicine and Infectious Disease, 2023)
In Sierra Leone, two operational research (OR) studies in 2019 and 2021 showed deficiencies in the data being captured by the Integrated Animal Disease Surveillance and Reporting (IADSR) system. This third OR study was conducted in 2023 to assess whether the second OR study’s results and recommendations were disseminated with the key stakeholders, the uptake of the recommendations, improvements in data capture in the IADSR system, and to describe the data on livestock disease and antimicrobial use. In 2022, on seven occasions, the authors of the second OR study disseminated the study’s findings. Of the four recommendations, the one on improving laboratory infrastructure for confirmation of animal disease was not implemented. The district animal health weekly surveillance reports received through the IADSR system were sustained at 88% between the second (2021) and third (2023) studies. In both studies, the proportion of sick animals receiving antibiotics (25%) remained the same, but the use of “critically important antimicrobials for veterinary use” declined from 77% (in 2021) to 69% (in 2023). The IADSR system has improved considerably in providing information on animal health and antibiotic use, and sequential OR studies have played a key role in its improvement.